2016
DOI: 10.1155/2016/7934257
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring with Micronuclei Test in Buccal Cells of Female Farmers and Children Exposed to Pesticides of Maneadero Agricultural Valley, Baja California, Mexico

Abstract: Feminization of the agricultural labor is common in Mexico; these women and their families are vulnerable to several health risks including genotoxicity. Previous papers have presented contradictory information with respect to indirect exposure to pesticides and DNA damage. We aimed to evaluate the genotoxic effect in buccal mucosa from female farmers and children, working in the agricultural valley of Maneadero, Baja California. Frequencies of micronucleated cells (MNc) and nuclear abnormalities (NA) in 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 27 publications
1
6
0
3
Order By: Relevance
“…Dividing the entire sample of participants in the study (exposed and unexposed children) into sub-groups (low, medium, and high OC concentrations), however, revealed a statistically-significant increase in TAC in the individuals with higher OC concentrations in their hair. The prevalences of MNi identified in both schools are important (58%), and the average value of the frequency of MNi in each child was 0.2%, close to the value that is considered the normal average of frequencies of micronuclei in children, which ranges from 0.1 to 3.6% 58,65 .…”
Section: Effects On Children's Healthsupporting
confidence: 52%
See 1 more Smart Citation
“…Dividing the entire sample of participants in the study (exposed and unexposed children) into sub-groups (low, medium, and high OC concentrations), however, revealed a statistically-significant increase in TAC in the individuals with higher OC concentrations in their hair. The prevalences of MNi identified in both schools are important (58%), and the average value of the frequency of MNi in each child was 0.2%, close to the value that is considered the normal average of frequencies of micronuclei in children, which ranges from 0.1 to 3.6% 58,65 .…”
Section: Effects On Children's Healthsupporting
confidence: 52%
“…Similar studies of the effects of pesticides on the frequency of MNi in buccal cells provide only inconsistent results 57 . Significant differences in the frequency of MNi have been demonstrated, for example, in women agricultural laborers with respect to an unexposed group 58 , while workers on banana plantations showed an increase in the frequency of micronuclei when compared to unexposed controls 59 . A study carried out with greenhouse workers found significant differences in nuclear alterations (MNi, BN,PK, KR) compared to a group that was not exposed to pesticides 60 ; however, those studies did not conduct analyses of pesticide concentrations that might reveal a direct association, but only considered potential exposures based on a list of the pesticides utilized.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have suggested that children have a high risk of exposure to pesticides through contact with environmental contaminants on the floor as well as through hand-to-mouth behavior with dust and soil. The latter represents a significant source of pesticide exposure (Simcox et al 1995, Castañeda-Yslas 2016. Furthermore, the results of the review by Deziel et al (2015) found five studies with evidence of cleaning practices that had a potential impact on the concentration of pesticides in the dust at home.…”
Section: Para-occupational Exposure: Women Living In Agricultural Fammentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Therefore, DNA damage varies considerably from one population to another.…”
Section: Dna Damages In Mexican Nativesmentioning
confidence: 99%